Kafka in a Skirt : Stories from the Wall - Chacón, Daniel (Camino del sol., 2019)
"A collection of short stories that grapples with the concept of a 'wall, ' both the literal partition along the U.S.-Mexico border and the less tangible walls that divide communities and peoples, particularly those who straddle more than one culture in their daily lives"--Provided by publisher.